Assessing consistency in the aerobic co-composting of faecal sludge and food waste in a municipality in Ghana - Nartey, Eric Gbenatey; Sakrabani, Ruben; Tyrrel, Sean; Cofie, Olufunke (Springer, 2023)
Background: A faecal sludge (FS) co-composting study assessed the extent of consistency in compost characteristics between and within batches. The study focused on the consistency of the co-composting process by measuring the variability of key parameters. Method: The set up consisted of 12 FS and food waste (FW) co-composting piles in three successive batches (1, 2 and 3). Consistency was assessed in the three successive batches of co-composted FS and food waste (FW). Within batches, consistency was assessed in each of them by dividing it into four separate replicate piles. Characteristics of interest were E. coli, as well as selected physico-chemical parameters (pH, EC, Mg, Ca, N, NH4-N, NO3-N, P, avail. P, and K) and heavy metals (Se, Fe, Cd, Cu, Hg, Ni, Pb and Cr). Data were subjected to analysis of variance (ANOVA) using SPSS. Result: Results show that, E. coli levels were not consistent between the successive batches during the entire co-composting process. While variations between batches were only observed for EC and nutrient parameters, variations were evident for several measured characteristics within batches. The measured coefficient of variations (CVs) within batches ranged between 0–125% and 3–111% for heavy metals and nutrients, respectively. Conclusion: In conclusion, there was less consistency in nutrients between successive batches and CV within batches was wide. Consistency levels for E. coli may not be an issue if pathogen inactivation is complete. Recommendation: It is recommended that a threshold value be created for determining what is an acceptable level of variation in FS co-composting.
Keywords: Faecal sludge; Co-composting; Variation; Traceability; Batch productions; Consistency; Food Waste